A simulation methodology for a system of product life cycle systems. (April 2018) - Kobayashi, Hideki; Matsumoto, Takuya; Fukushige, Shinichi
Abstract: To realize environmental sustainability, the flow of natural resources into industrial systems must be reduced and stabilized at a suitable level. One way to reduce resource flows in society is to establish resource-circulating manufacturing systems. To foster the circulation of resources in industry, life cycle simulation (LCS) technologies, which are based on discrete-event modeling, have been developed to dynamically evaluate the life cycles of products from resource extraction to end of life from both environmental and economic aspects. In reality, various industrial products interact with each other in unanticipated ways, and then these interactions affect the material flows in product life cycles. This type of complex system is called a system of systems (SoS). Focusing on this issue, we expand the evaluation's system boundary to include a system of multiple product life cycle systems. To handle an SoS quantitatively, we introduce typical types of interactions between product life cycle systems. The purpose of this study was to propose a new LCS methodology, called "LCS4SoS, " that focuses on an SoS consisting of different kinds of product life cycle systems. A prototype system of LCS4SoS was implemented based on this proposed methodology. Through a case study, it was found that the proposed methodology is useful for evaluating an SoS consisting of multi-product life cycle systems.